Development of Digital Learning Module on Archimedes Law material for Junior High School Students - Purwanti, Purwanti (WaPFi (Wahana Pendidikan Fisika), 2025)
This research aims to produce a digital learning module on Archimedes law material that is suitable for use by junior high school students. The research method used is a development method with the ADDIE model. This research is only up to the development stage. Validation was carried out by media experts and material experts and feasibility tests by 30 students. The results of the study were obtained that the validation of the material experts on the developed modules obtained a score of 85 with a good category. Media experts gave a score of 89.4 in the good category. The results of the feasibility test of students obtained a score of 84.7 with a good category. It can be concluded that the digital learning module on Archimedes' law developed is suitable for use by junior high school students.